2021
DOI: 10.3390/molecules26154654
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide Modifications against Clinically Isolated Antibiotic-Resistant Salmonella

Abstract: Antimicrobial peptides are promising molecules to address the global antibiotic resistance problem, however, optimization to achieve favorable potency and safety is required. Here, a peptide-template modification approach was employed to design physicochemical variants based on net charge, hydrophobicity, enantiomer, and terminal group. All variants of the scorpion venom peptide BmKn-2 with amphipathic α-helical cationic structure exhibited an increased antibacterial potency when evaluated against multidrug-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…While most known AMPs have a positive net charge (88% of AMPs on the APD3 have a net positive charge; [ 23 ]) only 4 AMPs in the APD3 have a net charge >20 (AP00411, AP00684, AP02232 and AP03367). Cationic AMPs are generally considered to interact with negatively charged bacterial membranes through electrostatic interactions [ 56 ] and, for some modified AMPs, increasing the peptide charge has resulted in more potent antimicrobial activity [ 57 59 ]. nAMP-LP-298 (GAGRWRANRRANRRRFARRLRRNQRRAAQKRRAHARRHQRNLRRAARKIRRIQRR-amide; see Table 7 ) was the only peptide tested in this study that displays activity against all bacterial species screened; this may be due to the high peptide charge which could be unravelled through further work.…”
Section: Resultsmentioning
confidence: 99%
“…While most known AMPs have a positive net charge (88% of AMPs on the APD3 have a net positive charge; [ 23 ]) only 4 AMPs in the APD3 have a net charge >20 (AP00411, AP00684, AP02232 and AP03367). Cationic AMPs are generally considered to interact with negatively charged bacterial membranes through electrostatic interactions [ 56 ] and, for some modified AMPs, increasing the peptide charge has resulted in more potent antimicrobial activity [ 57 59 ]. nAMP-LP-298 (GAGRWRANRRANRRRFARRLRRNQRRAAQKRRAHARRHQRNLRRAARKIRRIQRR-amide; see Table 7 ) was the only peptide tested in this study that displays activity against all bacterial species screened; this may be due to the high peptide charge which could be unravelled through further work.…”
Section: Resultsmentioning
confidence: 99%
“…While most known AMPs have a positive net charge [88% of AMPs on the APD3 have a net positive charge; 23] only 4 AMPs in the APD3 have a net charge >20 (AP00411, AP00684, AP02232 and AP03367). Cationic AMPs are generally considered to interact with negatively charged bacterial membranes through electrostatic interactions [54] and, for some modified AMPs, increasing the peptide charge has resulted in more potent antimicrobial activity [55-57]. nAMP-LP-298 (GAGRWRANRRANRRRFARRLRRNQRRAAQKRRAHARRHQRNLRRAARKIRRIQRR-amide; see Table 7) was only peptide tested in this study that displays activity against all bacterial species screened; this may be due to the high peptide charge which could be unravelled through further work.…”
Section: Resultsmentioning
confidence: 99%
“…The screening of derivatives from the AMP D51 against Bacillus cereus (a food poisoning bacterium) highlighted the peptides D51-P11G and D51-P11K for their anti-spore germination and anti-biofilm activities, which they instigated via membrane lysis [93]. Peptide variants of BmKn-2 from scorpion venom exhibited anti-biofilm activity against Salmonella isolates [94]. With respect to oral health, Jiang et al showed that AMP DP7 inhibited planktonic and biofilm forms of Porphyromonas gingivalis [95].…”
Section: Fungimentioning
confidence: 99%